MODEL PEMILIHAN CALON PESERTA LOMBA KOMPETENSI SISWA DENGAN METODE ANALYTICAL NETWORK PROCESS(ANP): STUDI KASUS SMKN 2 SUKABUMI - Denny Pribadi (Universitas Bina Sarana Informatika Kota Sukabumi, 2014)
Making a decision is very important in many cases, such as in determining the best students who will represent the school follows the Student Competency Competition (LKS). Because LKS winner from each city/county will follow the race up to the national and even international level. This study was made by using the Analytical Network Process (ANP) which is the process of counting algorithm to find the best decision by calculating the value criteria and comparing it to the calculation of the probability of each decision to be taken. This research will be used to help decision makers determine which students will be sent to the LKS-Vocational level cities. The criteria and sub-criteria used in the selection of students in accordance with existing procedures in SMK Negeri 2 Sukabumi is a personal evaluation (appearance, ethics, mental, creative,socially, height, sense of responsibility and the results of psychological tests), competency standards (rank, English and productive subjects) as well as school evaluation (interviews, discipline and parental support). Weighting and calculation of the results with the help of software Super Decision, the priority value given to three students who made alternative that Student A was 0.66092 , 0.17998 and Student B Student C was 0.15910